Fatty acids composition and total fat content in traditional foods from Black Sea Area countries - Albuquerque, T.G. (2013)
Objectives: This work was performed within the collaborative research program Sustainable exploitation of bioactive components from the Black Sea Area traditional foods (BaSeFood), funded by the European Commission. The overall objective of this study was to determine the total fat content and fatty acids (FA) composition among 33 traditional foods from six Black Sea Area countries (BSAC). Method: Total fat analysis was performed by an acid hydrolysis method with Soxhlet extraction (AOAC 948.15, 2000). Preparation of FA methyl esters was carried out by a combined method of methylation and transesterification. For FA determination chromatographic analysis was performed using a gas chromatograph with mass detector. FA methyl esters were separated in an Agilent HP-88 column (100 m x 0.25 mm i.d., 0.25 µm). Helium was the carrier gas. Split ratio of 50:1 and an injection volume of 1.0 µL were used. FA methyl esters were identified by comparing the retention times of the standards with those of the samples. Results: Total fat content ranged between 0.138 ± 0.0 g/100 g for Uzvar (Ukraine) and 99.9 ± 0.0 g/100 g for flax oil and mustard oil. From the 33 analysed traditional foods, 27.3% had fat contents below the limit of quantification (< 0.1 g/100 g). The highest content for saturated and polyunsaturated FA was found for flax oil (15.3 ± 0.6 g/100 g and 58.5 ± 0.5 g/100 g, respectively). Mustard oil showed the highest value for monounsaturated FA (55.1 ± 0.7 g/100 g), although it also has a high polyunsaturated FA content (38.0 ± 0.6 g/100 g of edible portion). Conclusions: In general, there was a great variability of results with respect to the FA profile of the analyzed traditional foods from BSAC, since there is a wide range of traditional foods from different countries and cultures. Some traditional foods from BSAC are a good source of unsaturated FA which are related to several health benefits. Acknowledgements: The research leading to these results has received funding from the European Community’s Seventh Framework Programme (FP7/2007-2013) under grant agreement n.º 227118.